The development of a learning management model with emphasis on practical implementation to promote computer literacy and skills for students' careers in computer club - Thaveesub, Nunthana (The Journal of Development Administration Research, 2020)
The research aimed (1) To study basic information and the need for computer teaching and learning for careers for students in computer club (2) To in order to develop a learning management model with emphasis on practical implementation to promote computer knowledge and practical skills for students in computer club (3) To try out the learning management model with emphasis on practical implementation to promote computer literacy and skills for students' careers in computer club (4) To in order to evaluate and improve the learning management model with emphasis on practical implementation to promote computer literacy and skills for students' careers in computer club. The population in the research was all secondary school students studied in computer club of Tedsabanthaklong one School, Academic year 2019, amount 40 students. The results of the research showed that (1) The development of a learning management model with emphasis on practical implementation is necessary. School administrators, Basic Education Commission, Parents, Communities, the teachers and the supervisor of learner development activities agreed with the necessity and appropriateness of the model development. Students interested and want to learn more about basic computer programs, especially computers for careers. (2) There is a learning management model with emphasis on practical implementation to promote computer literacy and skills for students' careers in computer club. (3) Learning management model with emphasis on practical implementation Effective 83.45 / 81.08 (4) Learning achievement from teaching with emphasis on practical implementation model showed that the standard score (T score) of after studying was higher than before studying. The average score increased by 18.98. The overall of practice skills from the study were in a very good level. The overall of students' satisfaction with the teaching model was at the highest level. And there is a complete improvement to the APPA Model.